Prospects of gas hydrate presence in the Chukchi Sea - Matveeva T.V.; Semenova A.A.; Shchur N.A.; Logvina E.A.; Nazarova O.V. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2017)
The purpose of this study is to forecast the scale and distribution character of gas hydrate stability zone in the Chukchi Sea under simulated natural conditions and basing on these results to estimate resource potential of gas hydrates within this area. Three types of stability zone have been identified. A forecast map of gas hydrate environment and potentially gas hydrate-bearing water areas in the Chukchi Sea has been plotted to a scale of 1:5 000 000. Mapping of gas hydrate stability zone allowed to give a justified forecast based on currently available data on geologic, fluid dynamic, cryogenic, geothermal and pressure-temperature conditions of gas hydrate formation in the Chukchi Sea. It is the first forecast of such kind that focuses on formation conditions for hydrates of various types and compositions in the Arctic seas offshore Russia. Potential amount of gas, stored beneath the Chukchi Sea in the form of hydrates, is estimated based on mapping of their stability zone and falls into the interval of 7·1011-11.8·1013 m3.
Keywords: Chukchi Sea; gas hydrates; methane; hydrocarbon gases; gas hydrate stability zone; potentially gas hydrate-bearing water areas; resources